THE PHENOMENOLOGY OF ELEGANCE: AN OUTLINE - Andrei SIMIONESCU-PANAIT (Studia Universitatis Babeș-Bolyai. Philosophia)
Elegance ranks low on the list of debated topics in philosophy, mainly because of the fleeting and mundane character of phenomena that it relies on for its existence. However, the rise of kinaesthesia as an important topic in today’s philosophical and phenomenological environment facilitates the inclusion of elegance in the canon of philosophical debates. This article reviews two important positions regarding elegance, that of Renaissance philosopher Baldassare Castiglione and of 20th Century realist phenomenologist Dietrich von Hildebrand. First, we underline three aspects of Castiglione’s concept of sprezzatura and showcase the significance and purpose of practicing elegance. This step is succeeded by a close look at von Hildebrand’s attachment to a realist phenomenological frame for understanding why he denies elegance the status of an ideal value. Last, we look at the connection between elegance and three ideas from a hybrid phenomenology from Husserl and Sheets-Johnstone. These connections form the basis for filling the significant gap between Castiglione’s Renaissance take on elegance and von Hildebrand’s realist perspective with a new phenomenological project regarding elegance.